Resin-Mxene composite for electromagnetic shielding applications - Azka Rehman,; Nur Azreen Azhar,; Huda A Majid,; Herdawatie Abdul Kadir,; Fahmiruddin Esa, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The growing demand for advanced electromagnetic interference (EMI) shielding materials has driven the development of lightweight high-performance solutions for modern electronics. In this study, Mo2Ti2C3 MXene was synthesized via selective etching of the Mo2Ti2AlC3 MAX phase using hydrofluoric acid (HF) at concentrations of 6M and 9M. The synthesized MXene was then incorporated into a resin matrix to fabricate MXene-based composites with varying filler loadings of 1 wt.%, 3 wt.%, and 5 wt.% for EMI shielding applications. Fourier-transform infrared spectroscopy (FTIR) confirmed that 9M HF etching resulted in higher surface functionalization, with pronounced –OH, –O, and –F terminations, which enhanced electrical conductivity. Field-emission scanning electron microscopy (FESEM) showed a morphological transition from a compact MAX phase to a characteristic stacked lamellar MXene structure, while energy-dispersive X-ray spectroscopy (EDX) validated the complete removal of aluminum. X-ray diffraction (XRD) analysis demonstrated that the incorporation of 3 wt.% MXene into the resin matrix yielded the highest crystallinity, suggesting strong interfacial interactions. Reflection coefficient (S11) measurements in the X-band (8.2–12.4 GHz) showed that a higher MXene content enhanced wave reflection, improving EMI shielding. The 3 wt.% MXene composite achieved optimal performance by balancing reflection and absorption, minimizing transmitted interference. These findings demonstrate that the 9M HF-etched Mo2Ti2C3 MXene with 3 wt.% filler loading provides the best balance of electrical conductivity, structural stability, and EMI shielding effectiveness, making it a promising candidate for next-generation electronic and communication applications.